(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current implementation of the essential care for mothers and newborns immediately after normal delivery at the Obstetrics Department of the National Hospital of Obstetrics and Gynecology in 2024. Research subjects: Midwives directly participating in delivering full-term pregnancies at the time of the study; mothers and newborns were healthy. Research methods: Cross-sectional description, observing 141 cases of practice of care for mothers and newborns during and immediately after birth. The assessment scale for the essential care for mothers and newborns immediately after birth consists of 19 sub-items with the maximum total score of the essential care for mothers and newborns immediately after birth being 38 points. Results: Average essential care score 37.87 ± 0.36 points. 100% of midwives in the study practiced essential care for mothers and newborns during and immediately after birth with very good ratings (from 36-38 points). The majority (89.4%) achieved the maximum score (38 points). Conclusion: Midwives performed essential care procedures for mothers and newborns very well, but still need to improve their skills in essential care for mothers and newborns during and immediately after birth.